POVERTY AND SUSTAINABLE SOCIO-ECONOMIC DEVELOPMENT IN AFRICA: THE NIGERIA EXPERIENCE - Ighodalo, Akhakpe (European Scientific Journal, ESJ, 2012)
The paper argues that poverty has remained a major obstacle to sustainable development and democracy in the global South. With the return to civil rule in 1999 in Nigeria, hopes were high that the return to democracy will stem the decline of the economy and provide the citizenry with the social dividends of democracy. More than a decade after the economy is still on it’s kneels with more than half of the population living on less than one dollar per day. With the use of dependency theory the paper posited that unless the people are empowered to make choices and participate in making decisions that affects their lives sustainable socio-economic development will remain elusive in Africa in general and Nigeria in particular.